Human, social and financial capital factors that influence the success of black-owned small business in South Africa - Lubita, Susan Mpho (My University, 2017)
In South Africa, developing small businesses is one of the strategies that the government is using to reduce unemployment and by doing so alleviate poverty and inequality (National Planning Commission, 2011). According to the National Development Plan, 90% of new jobs will be created by Small and Medium Enterprises (SMEs) by 2030 (National Planning Commission, 2011) yet the Global Entrepreneurship Monitor (GEM) South African Report for 2015/2016 reveals that conditions in South Africa remain unsupportive of small business. It is therefore imperative to address the shortcomings within the entrepreneurial ecosystem in order to improve the success rates of small businesses in South Africa. This qualitative study is a case study of human, social and financial capital factors that influence business success of small black-owned business. Twelve (12) participants, who represented previous or current small business owners, were selected to be interviewed as part of the study. The study’s main findings were that Entrepreneurship specific investments in human capital result in a higher positive impact on overall business performance in contrast to general investments in human capital. Strong social capital ties positively impact business performance more in the start-up phase of a business. Weak social capital ties positively impact business performance more in the growth phase of a business and that financial capital positively impacts overall business performance. The research also found an interplay between human, social and financial capital as they relate to business performance. There is a requirement for future research to investigate which human, social and financial capital factors maximise business success.
MBA
Keywords: Small business -- South Africa. Small business -- Finance.